Formation of plastic properties during deformation stretching of pearlitic steel - V. P. Fetisov (Литьë и металлургия)
Under tensile deformation, the effect of pearlite fineness and strain hardening parameters under uniform and local deformation on the plastic properties of high‑carbon steel has been studied. The increase in the plasticity of pearlitic steel with a thin‑lamellar structure is due to an increase in the intensity of strain hardening in the region of concentrated deformation and an increase in the deformability of cementite plates. For the structures of thin‑lamellar pearlite, the ratio between the interlamellar distance and the value of the relative narrowing is given.